Sustainable Energy Systems: From Primary to End-Use - Godina, Radu (MDPI - Multidisciplinary Digital Publishing Institute, 2019)
This book focuses on sustainable energy systems. While several innovative and alternative concepts are presented, the topics of energy policy, life cycle assessment, thermal energy, and renewable energy also play a major role. Models on various temporal and geographical scales are developed to understand the conditions of technical as well as organizational change. New methods of modeling, which can fulfil technical and physical boundary conditions and nevertheless consider economic environmental and social aspects, are also developed.